Insights Into Transcriptome Profiles Associated With Wooden Breast Myopathy in Broilers Slaughtered at the Age of 6 or 7 Weeks - Malila, Yuwares; Uengwetwanit, Tanaporn; Thanatsang, Krittaporn V.; Arayamethakorn, Sopacha; Srimarut, Yanee; Petracci, Massimiliano; Soglia, Francesca; Rungrassamee, Wanilada; Visessanguan, Wonnop (Frontiers in Physiology, 2021)
Wooden Breast (WB) abnormality has a severe economic impact in the broiler industry. Transcriptomes associated with WB were characterized in broilers at two different market ages. Breasts (Pectoralis major) were collected, 20-min postmortem, from male Ross 308 broilers slaughtered at 6 (6wk) and 7 weeks (7wk) of age. The breasts were classified as “non-WB” or “WB” based on palpation hardness scoring (non-WB = no abnormal hardness, WB = consistently hardened). Total RNA was isolated from 16 samples (n = 3 for 6wk non-WB, n = 3 for 6wk WB; n = 5 for 7wk non-WB, n = 5 for 7wk WB). Transcriptome was profiled using a chicken gene expression microarray with one-color hybridization technique, and compared between non-WB and WB samples of the same age. Among 6wk broilers, 910 transcripts were differentially expressed (false discovery rate, FDR < 0.05). Pathway analysis underlined metabolisms of glucose and lipids along with gap junctions, tight junction, and focal adhesion (FA) signaling as the top enriched pathways. For the 7wk broilers, 1,195 transcripts were identified (FDR < 0.05) with regulation of actin cytoskeleton, mitogen-activated protein kinase signaling, protein processing in endoplasmic reticulum and FA signaling highlighted as the enriched affected pathways. Absolute transcript levels of eight genes (including actinin-1 - ACTN1, integrin-linked kinase - ILK, integrin subunit alpha 8 - ITGA8, integrin subunit beta 5 - ITGB5, protein tyrosine kinase 2 - PTK2, paxillin - PXN, talin 1 - TLN1, and vinculin – VCL) of FA signaling pahtway were further elucidated using a droplet digital polymerase chain reaction. The results indicated that, in 6wk broilers, ITGA8 abundance in WB was greater than that of non-WB samples (p<0.05). Concerning 7wk broilers, greater absolute levels of ACTN1, ILK, ITGA8, and TLN1, accompanied with a reduced ITGB5 were found in WB compared with non-WB (p<0.05). Transcriptional modification of FA signaling unlerlined the potential of disrupted cell-cell communication that may incite aberrant molecular events in association with development of WB myopathy.